FORMATION OF SPINEL STRUCTURE IN SYNTHESIS PROCESS OF Li1.37Mn2O4 USING HYDROTHERMAL METHOD - Ibrahim Purawiardi; Etty Wigayati (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2018)
FORMATION OF SPINEL STRUCTURE IN SYNTHESIS PROCESS OF Li1.37Mn2O4 USING HYDROTHERMAL METHOD. Li1.37Mn2O4 is one form of Li1+xMn2O4 which is engineered from LiMn2O4 phase which is commonly used as a lithium cathode active ingredient. The crucial thing from Li1.37Mn2O4 synthesis is the spinel structure that is formed. This study aims to observe when the spinel structure of Li1.37Mn2O4 starts and when the transformation from a tetragonal structure into spinel occurs. The raw materials used are tetragonal LiOH and tetragonal MnO2. The synthesis was carried out using a hydrothermal method with a temperature of 200 oC with a variation of holding times of 50, 70, 90 and 110 hours. Observation of spinel structure was carried out using XRD and TEM. The results obtained were at the holding times of 50 and 70 hours, the spinel structure had not been formed. The spinel structure begins to form at 90 hours holding time which also indicates that the transformation from the tetragonal structure to spinel occurs at such holding time. The result of a 90-hour holding time is a regular spinel structure but there are still many Mn and Mn-O –based impurities. While the results of the 110-hour holding time produce a perfect yet irregular transformation of the spinel structure.